2015
DOI: 10.1038/ncomms8239
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of tetraacylated phosphatidylinositol hexamannoside and evaluation of its immunomodulatory activity

Abstract: Tuberculosis, aggravated by drug-resistant strains and HIV co-infection of the causative agent Mycobacterium tuberculosis, is a global problem that affects millions of people. With essential immunoregulatory roles, phosphatidylinositol mannosides are among the cell-envelope components critical to the pathogenesis and survival of M. tuberculosis inside its host. Here we report the first synthesis of the highly complex tetraacylated phosphatidylinositol hexamannoside (Ac2PIM6), having stearic and tuberculosteari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…PIM2 and synthetic PIM2 analogs have been designed for use of experimental adjuvants (Ainge et al, 2006;Parlane et al, 2012;Patil et al, 2015;Sprott et al, 2004;Zheng et al, 2015). The identification of a novel PIM2 receptor may provide a molecular basis for the development of efficient adjuvants for therapeutic vaccines against not only tuberculosis but also other infectious diseases, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PIM2 and synthetic PIM2 analogs have been designed for use of experimental adjuvants (Ainge et al, 2006;Parlane et al, 2012;Patil et al, 2015;Sprott et al, 2004;Zheng et al, 2015). The identification of a novel PIM2 receptor may provide a molecular basis for the development of efficient adjuvants for therapeutic vaccines against not only tuberculosis but also other infectious diseases, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The glycolipids lipomannan and AcPIM 2 are native constituents of the cell envelope of the Corynebactereae family that includes pathogenic M. tuberculosis 28 , 29 . They contribute to the low permeability of the cell envelope and the intrinsic tolerance against antibiotics 30 and can sabotage immunoregulatory responses 31 . In addition, a lycopene molecule is resolved in a narrow tunnel of QcrB close to the Q o site and with access to the intercomplex cavity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It can also activate NKT cells together with CD1 molecules to produce IFN-γ, interact with α5β1 on CD4 + T cells to promote granulomatous formation and promote alveolar epithelial cell apoptosis ( Rojas et al., 2006 ). Recent research has shown that tetraacylated phosphatidylinositol hexamannoside (Ac2PIM6), which is synthesized with stearic and tuberculostearic acid as the lipid components, could increase the production of IL-4 and IFN-γ in mouse serum and have comparable adjuvant activity ( Patil et al., 2015 ). Therefore, the immunotherapeutic effect of PIMs on TB requires further verification.…”
Section: Chemical Agentsmentioning
confidence: 99%